Adat Budaya Sasamben Budak Bujang (Benjang) Di Kecamatan Ujungberung Kota Bandung - Habib Indraswara; Tri Cahyanto (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
The Sasamben Budak Bujang (Benjang) culture is a traditional arts tradition that combines art and martial arts, which developed in the people of the Ujungberung area of ​​Bandung City. This culture involves the use of plants in the implementation process. Information regarding the plants used in these traditional processes has not been widely reported. The aim of this research is to find out the types of plants used in the benjang tradition. Benjang art in the customs or culture of the Ujungberung people, East Bandung City, West Java Province, has a special position when compared with other arts. Benjang Gulat is the initial form of benjang art, over time the benjang art developed into three types, namely benjang helaran, benjang wrestling or gelut and benjang mask. Benjang Ujungberung has been known to many among the Ujungberung community since the end of the 19th century or the beginning of the 20th century, as a game played on an amben or bale which is called sasamben by some bujang, which means boys. In the special benjang event, various kinds of plants are used, such as bananas, coconut dawegan, seven kinds of flowers, brown sugar, granulated sugar, bitter coffee and cigarettes.